CODE SWITCHING PERFORMED BY ENGLISH TEACHER IN TEACHING AND LEARNING PROCESS IN ZUMROTUS SALAMAH PRIMARY SCHOOL - Rohman, Amik Kholilu (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT The phenomenon of code-switching in bilingual education serves as a crucial bridge in facilitating second language acquisition, particularly at the elementary school level where English is still considered a foreign language. This study focuses on analyzing the linguistic practices of an English teacher at Zumrotus Salamah Elementary School, with the primary goal of identifying the types of code-switching used and the underlying pedagogical reasons. Using a descriptive qualitative approach, this study collected data through in-depth classroom observations, interviews, and documentation, which were then analyzed based on Poplack and Hoffman's theoretical framework. The findings revealed that the teacher actively switched between English, Indonesian, and Arabic through three specific categories: extra-sentential, intra-sentential, and inter-sentential, with the intra-sentential type appearing most dominant. This language switching was not random but rather a conscious strategy aimed at clarifying meaning, emphasizing instruction, checking student understanding, and maintaining group identity. This study concludes that code-switching is not an indication of a lack of linguistic competence but rather an effective and adaptive pedagogical strategy that supports student understanding and maintains interactive communication in a bilingual classroom environment. ABSTRAK Fenomena alih kode dalam pendidikan bilingual berfungsi sebagai jembatan krusial dalam memfasilitasi pemerolehan bahasa kedua, khususnya di tingkat sekolah dasar di mana bahasa Inggris masih dianggap sebagai bahasa asing. Penelitian ini berfokus pada analisis praktik linguistik seorang guru bahasa Inggris di SD Zumrotus Salamah, dengan tujuan utama mengidentifikasi jenis-jenis alih kode yang digunakan serta alasan pedagogis yang mendasarinya. Menggunakan pendekatan kualitatif deskriptif, penelitian ini mengumpulkan data melalui observasi kelas yang mendalam, wawancara, dan dokumentasi, yang kemudian dianalisis berdasarkan kerangka teori Poplack dan Hoffman. Temuan penelitian mengungkapkan bahwa guru secara aktif melakukan pergantian antara bahasa Inggris, Indonesia, dan Arab melalui tiga kategori spesifik: extra-sentential, intra-sentential, dan inter-sentential, di mana tipe intra-sentential muncul paling dominan. Peralihan bahasa ini terbukti bukan terjadi secara acak, melainkan merupakan strategi sadar yang bertujuan untuk mengklarifikasi makna, menekankan instruksi, memeriksa pemahaman siswa, serta menjaga identitas kelompok. Penelitian ini menyimpulkan bahwa alih kode bukanlah indikasi kekurangan kompetensi linguistik, melainkan sebuah strategi pedagogis yang efektif dan adaptif yang mendukung pemahaman siswa serta menjaga keberlangsungan komunikasi interaktif dalam lingkungan kelas bilingual.